2019
DOI: 10.4049/jimmunol.1801032
|View full text |Cite
|
Sign up to set email alerts
|

Protease-Activated Receptor 1 Deletion Causes Enhanced Osteoclastogenesis in Response to Inflammatory Signals through a Notch2-Dependent Mechanism

Abstract: We found that protease-activated receptor 1 (PAR1) was transiently induced in cultured osteoclast precursor cells. Therefore, we examined the bone phenotype and response to resorptive stimuli of PAR1-deficient (knockout [KO]) mice. Bones and bone marrow-derived cells from PAR1 KO and wild-type (WT) mice were assessed using microcomputed tomography, histomorphometry, in vitro cultures, and RT-PCR. Osteoclastic responses to TNF-a (TNF) challenge in calvaria were analyzed with and without a specific neutralizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 60 publications
0
9
1
Order By: Relevance
“…Interestingly, Jastrzebski et.al. detected the p65 expression in cytoplasmic and nuclear under RANKL (30 ng/ml) stimulated 15 min, and found no significant differences between control and F2r-defcienct cell [45]. In our study, F2r knockdown increased p65 and IKBα phosphorylation level under RANKL (10 ng/ml) stimulated at 5 min and 10 min, indicating that F2r responds to RANKL signaling at early stages of osteoclastogenesis.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Interestingly, Jastrzebski et.al. detected the p65 expression in cytoplasmic and nuclear under RANKL (30 ng/ml) stimulated 15 min, and found no significant differences between control and F2r-defcienct cell [45]. In our study, F2r knockdown increased p65 and IKBα phosphorylation level under RANKL (10 ng/ml) stimulated at 5 min and 10 min, indicating that F2r responds to RANKL signaling at early stages of osteoclastogenesis.…”
Section: Discussioncontrasting
confidence: 45%
“…al. demonstrated that F2r deletion causes enhanced osteoclastogenesis [45]. However, the functions of F2r for osteoclast acidification, differentiation, activation, and bone resorption are still unknown; and without detailed mechanism studies, the mechanisms underlying the role of F2r in osteoclastogenesis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed an increase in urokinase plasminogen activating factor production following LPS treatment, and it is believed that subsequent plasmin production activated PAR-1 and reduced osteoclast formation [40]. These data were supported by another study showing that osteoclastogenesis was enhanced in PAR-1 knockout mice treated with TNFalpha, indicating that PAR-1 acts as an inhibitor of osteoclast maturation in inflammatory joint diseases [54]. In a model of tibial damage, bone repair was found to be inhibited in PAR-1 knockout mice while thrombin improved bone marrow stromal cell proliferation in a PAR-1-dependent manner [24,55].…”
Section: Par-1 and Jointsmentioning
confidence: 78%
“…[62][63][64] Tudpor et al also reported an increased bone volume in Par1-knockout mice, which contrasted with the data of Aronovich et al 45,61 Furthermore, another group found that the difference was slight and although the bone mass was decreased in Par1-knockout mice, deficiency of PAR-1 resulted in osteoclastogenesis via the Notch receptor 2 (NOTCH2) signaling pathway, and overexpression of PAR-1 significantly inhibited the osteoclastogenic response. 65 In addition to its effects on osteoblasts, Sivagurunathan et al 66 reported that thrombin inhibited osteoclastogenesis. Furthermore, they found that thrombin inhibited osteoclast differentiation of different organs in Par-1 knockout mice, which suggested that the PAR-1 pathway was not involved in thrombin-induced downregulation of osteoclastogenesis.…”
Section: Thrombin and Protease-activated Receptorsmentioning
confidence: 99%